2009
DOI: 10.1029/2008gl037050
|View full text |Cite
|
Sign up to set email alerts
|

Surface age of surface renewal in turbulent interfacial transport

Abstract: [1] We use direct numerical simulation to study characteristics of interfacial transfer of gas and heat in free-surface turbulence. Using Lagrangian tracing, we are able to directly quantify surface age of surface renewal for the first time. The physical meaning of surface renewal and various representations of surface age, including the use of heat as a proxy, are discussed. Results show that the Higbie penetration theory and the Danckwerts random surface renewal model are inappropriate for gas transfer. [2] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Several studies have shown that the Kolmogorov distribution function (a log-normal distribution) was more appropriate (e.g. Garbe et al, 2004;Kermani and Shen, 2009). This said, the average surface age from Dankckwerts' random surface renewal model was surprisingly close to hybrid Lagrangian tracing and temperature method, the state of the art in gas transfer modelling at the interface between a liquid and the atmosphere (Kermani et al, 2011).…”
Section: 1mentioning
confidence: 98%
“…Several studies have shown that the Kolmogorov distribution function (a log-normal distribution) was more appropriate (e.g. Garbe et al, 2004;Kermani and Shen, 2009). This said, the average surface age from Dankckwerts' random surface renewal model was surprisingly close to hybrid Lagrangian tracing and temperature method, the state of the art in gas transfer modelling at the interface between a liquid and the atmosphere (Kermani et al, 2011).…”
Section: 1mentioning
confidence: 98%
“…The surface age can be thought of as the time between two surface renewal events. Kermani & Shen (2009) concluded that Higbie's model is inappropriate for describing the gas transfer and Danckwert's model is only applicable at large surface age where the gas transfer is actually insignificant. Hasegawa & Kasagi (2009) performed a hybrid DNS/LES calculation of a coupled air-water turbulent flow and associated mass transfer for Sc = 1 and 100 at Re τ = 150 (Re τ is the Reynolds number based on the interfacial friction velocity).…”
Section: Introductionmentioning
confidence: 99%
“…Magnaudet & Calmet (2006) used a large-eddy simulation (LES) to perform a statistical analysis of the structure of the near-surface region of an open-channel flow at a high Reynolds number. Kermani & Shen (2009) used DNS to study characteristics of interfacial mass transfer driven by free-surface turbulence. They investigated the quantification of the surface age related to the surface renewal models pioneered by Higbie's penetration theory (Higbie 1935) and further elaborated by Danckwert's random surface renewal model (Danckwerts 1951).…”
Section: Introductionmentioning
confidence: 99%
“…For example, at the UP3 station, peaks appeared approximately every ten minutes, resulting in 6% variability in the enrichment of FDOM. Although seemingly small, this variability nevertheless indicates that surface renewal, potentially enhanced by advection in upwelling regions (Kermani and Shen, 2009;Thomas et al, 2013), occurs within very short time intervals. At the UP2 station (Figure 3b), the temporal decrease in FDOM enrichment was caused by increasing FDOM concentrations in bulk water as the catamaran approached the front (Ribas-Ribas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%